MicroRNA-381—A Key Transcriptional Regulator: Its Biological Function and Clinical Application Prospects in Cancer - Zeng, Xue; Cao, Zhe; Luo, Wenhao; Zheng, Lianfang; Zhang, Taiping (Frontiers in Oncology, 2020)
MicroRNAs (miRNAs) are a small noncoding RNA molecules that function by regulating messenger RNAs. Recent studies have shown that miRNAs play important roles in multiple processes of cancer development. MiR-381 is one of most important miRNAs in cancer progression. MiR-381 is downregulated in some cancers and upregulated in other cancers, including glioma, epithelial sarcoma and osteosarcoma. MiR-381 regulates epithelial–mesenchymal transition (EMT), chemotherapeutic resistance, radioresistance, and immune responses. Thus, miR-381 participates in tumor initiation, progression, and metastasis. Moreover, miR-381 functions in various oncogenic pathways, including the Wnt/β-catenin, AKT, and p53 pathways. Clinical studies have shown that miR-381 could be considered a biomarker or a novel prognostic factor. Here, we summarize the present studies on the role of miR-381 in cancer development, including its biogenesis and various affected signaling pathways, and its clinical application prospects. MiR-381 expression is associated with tumor stage and survival time, making miR-381 a novel prognostic factor.